Internet Resources for Translating Kant - Naragon, Steve (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This article gathers together various internet resources that are available for translator’s of Kant’s texts, including resources for digital texts of Kant’s and historically-relevant other writings, digital catalogs of published books and periodicals, online dictionaries, and digitally available 18th/19th century monolingual and bi-lingual dictionaries, encyclopedia, and Kant-specific lexicons.